Kedudukan dan peran kompilasi hukum ekonomi syariah dalam sistem hukum nasional - Al Athif, Muhammad Alif; Al Zam Zami, Advia Kusuma; Al Hasani, Habibul Mahbub; Arfan, Abbas (Maliki Interdisciplinary Journal, 2026)
The Compilation of Sharia Economic Law (KHES) is a codified legal framework established to provide legal certainty and guidance in the practice of sharia-based economic activities in Indonesia. This article examines KHES systematically, covering its historical background, drafting methodology, legal substance, and structural arrangement. Furthermore, this study analyzes the position of KHES within the national legal system, particularly in relation to its juridical and authoritative functions in sharia economic practices. The findings indicate that KHES plays a significant role as a juridical basis for resolving sharia economic disputes. By exploring these aspects, this paper aims to strengthen academic understanding of the strategic position of KHES as a normative instrument that bridges Islamic law and the national legal system. The integration of sharia principles and positive law is expected to serve as a foundational basis for the development of a more comprehensive and practically applicable sharia economic legal system within the national legal framework.